Road Of Stars To Santiago - Stanton, Edward F., 1942- (Book collections on Project MUSE., 2015)
In the tradition of Colin Fletcher's The Man Who Walked Through Time and William Least Heat-Moon's Blue Highways, Edward F. Stanton has written a quietly beautiful and engrossing account of his own pilgrimage. Road of Stars to Santiago is a personal story of his journey along what has been called ""the premier cultural route of Europe."" ""I undertook a five-hundred-mile walk along the ancient Camino de Santiago, from the French Pyrenees to Santiago de Compostella in northwest Spain, the supposed burial site of the apostle St. James the Elder, and beyond to Finisterre, Land's End on the Atl.